Impact of cyclosporine A concentration on acute graft‐vs‐host disease incidence after haploidentical hematopoietic cell transplantation. (14th May 2019) - Stocker, Nicolas; Duléry, Remy; Battipaglia, Giorgia; Brissot, Eolia; Médiavilla, Clémence; Sestili, Simona; Paviglianiti, Annalisa; Ledraa, Tounes; Mohty, Razan; Bazarbachi, Abdulhamid; Belhocine, Ramdane; Vekhoff, Anne; et al.
Abstract: Objectives: This retrospective study analyzed the impact of early cyclosporine A (CsA) initiation (day −3) on the risk of acute graft‐vs‐host disease (aGvHD) after haploidentical hematopoietic cell transplantation (Haplo‐HCT) using post‐transplant cyclophosphamide. Methods: Sixty‐one consecutives patients who underwent Haplo‐HCT were analyzed. Results: At day +180, the cumulative incidences of grade II‐IV and grade III‐IV aGvHD were 39% and 18%, respectively. Patients having a lowest CsA concentration (<301 ng/mL; the cutoff value used to segregate the patients between low and high CsA concentrations) in the first week after Haplo‐HCT had a significantly higher risk of grade II‐IV aGvHD ( P = 0.02), severe grade III‐IV aGvHD ( P = 0.03), cGvHD ( P = 0.02), and extensive cGvHD ( P = 0.04). In multivariate analysis, a higher CsA concentration (≥301 ng/mL) during the first week following Haplo‐HCT was the only parameter significantly associated with a reduced risk of grade II‐IV and grade III‐IV aGvHD (RR = 0.21; P = 0.049 and RR < 0.001; P < 0.0001, respectively). We find no correlation between CsA concentration and relapse, non‐relapse mortality, progression‐free survival, GvHD‐free and progression‐free survival, or overall survival. Conclusions: CsA could be initiated early before Haplo‐HCT with achievement of high CsA concentration to reduce the risk of aGvHD without any detrimental effect on relapse.